2010
DOI: 10.9755/ejfa.v22i2.4896
|View full text |Cite
|
Sign up to set email alerts
|

Variation of yield, milling, technological and rheological characteristics in some Egyptian bread wheat (Triticum aestivum L.) cultivars

Abstract: A field experiment was conducted to evaluate yield, milling, technological and rheological characteristics of four Egyptian bread wheat cultivars (Gemmeiza 7, Gemmeiza 9, Sakha 93 and Giza 168). Results showed that Gemmeiza 9 had the highest number of spikes per m 2 , number of grains per spike and grain yield. Gemmeiza 7 had the highest fine and coarse bran, protein, wet and dry gluten percentages as well as the best farinograph and extensograph properties (dough development time, dough stability time and dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 2 publications
8
19
1
Order By: Relevance
“…The result of this study was in line with that of Osman and Mohamed (1981) who reported that abundant supply of seed rates delay physiological maturity in wheat. The result was also in agreement with Seleiman et al (2010) who reported that increasing seeding rates from 250-400 mG 2 grains prolong the number of days from sowing to maturity of wheat. In contrast, Melaku (2008) reported that increasing levels of seed rate promoted early physiological maturity of tef.…”
Section: Days To 90% Physiological Maturitysupporting
confidence: 92%
See 1 more Smart Citation
“…The result of this study was in line with that of Osman and Mohamed (1981) who reported that abundant supply of seed rates delay physiological maturity in wheat. The result was also in agreement with Seleiman et al (2010) who reported that increasing seeding rates from 250-400 mG 2 grains prolong the number of days from sowing to maturity of wheat. In contrast, Melaku (2008) reported that increasing levels of seed rate promoted early physiological maturity of tef.…”
Section: Days To 90% Physiological Maturitysupporting
confidence: 92%
“…Similar result was obtained by Salem (1999) who found that increasing seeding rate from 60 up to 120 kg haG 1 delayed the flowering and maturity of wheat crop. Likewise, Seleiman et al (2010) reported that increasing seeding rates from 250-400 mG 2 grains caused a significant increase in the number of days from sowing to 50% heading in wheat. In contrast, Gafaar (2007) found that increasing sowing density from 200 up to 400 grains per meter square in wheat crop significantly decreased the number of days to 50% heading.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, Iqbal et al, (2012) also found that biological yield was increased as seeding rate increased from 125 kg ha -1 to 150 and 175 kg ha -1 . Moreover, Seleiman et al (2010) confirmed that increasing seeding rates up to 350 or 400 grains m -2 increased grain, straw and biomass yields.…”
Section: Biomass Yield (Kg Ha -1 )supporting
confidence: 57%
“…Gafaar (2007) also stated that increasing sowing density from 200 up to 400 grains m -2 significantly decreased spike length. Similarly, Seleiman et al (2010) reported that the longest spikes were obtained from 250 and 300 grains per m 2 but without significant differences between both of them.…”
Section: Resultsmentioning
confidence: 85%